Food safety compliance readiness of Kansas pet food manufacturers - Schmidt, Darby L.; Jones, Cassandra K. (My University, 2017)
A new food safety law, the Food Safety Modernization Act, has increased regulatory expectations for pet food manufacturers. A 13-question survey was developed and disseminated electronically to 233 Kansas pet food manufacturers by the Kansas Department of Agriculture. The objectives of this survey were to 1) evaluate the readiness of Kansas pet food manufacturers for the new compliance expectations, and 2) determine the preferred delivery method for supplementary food safety training. A total of 32 responses were completed (13.7% response rate). Descriptive statistics for continuous variables were analyzed using proc surveymeans, and paired t-tests were analyzed using proc ttest of SAS v9.4 (SAS Inst., Cary, NC). Even though the law was passed in 2011, and compliance dates begin this year, over 42% of respondents were only somewhat familiar with the Food Safety Modernization Act or its potential impact on their facility. Still, 47% of respondents felt confident that their facility would pass an inspection for hazard analysis and risk-based preventive controls by the Food and Drug Administration. Two of the requirements for passing this inspection are 1) documented training on animal food safety and animal food hygiene and 2) expectations for a Preventive Controls Qualified Individual. However, only 28% of facilities had documented training in this area, and only 50% of facilities had identified their Preventive Controls Qualified Individual. Based on these findings, it was determined that a number of Kansas pet food manufacturers either do not understand the new food safety requirements or are unprepared for their implementation. Facilities recognize this constraint. A total of 76% of respondents reported that they would utilize food safety training, which was greater (P < 0.05) than those who indicated it would not be of use. The survey also asked for the facilities’ preference for training delivery methods by ranking from 1 to 4, with 1 being ideal. Respondents reported their preference would be online in multiple 10-minute lectures (mean score 1.96) or online in multiple 30-minute lectures (mean score 2.00), which was preferred (P < 0.05) to a blended course of online and face-to-face components (mean score 2.61). All three options were preferred (P < 0.05) to face-to-face only (mean score 3.41). In summary, Kansas pet food manufacturers indicated a need for additional training in the new food safety regulation, with the preferred method of delivery occurring online.
Keywords: Fall 2017